Tectus niloticus (Tegulidae, Gastropod) as a Novel Vector of Ciguatera Poisoning: Detection of Pacific Ciguatoxins in Toxic Samples from Nuku Hiva Island (French Polynesia) - Darius, Hélène Taiana (Toxins (Basel), 2017)
Ciguatera fish poisoning (CFP) is a foodborne disease caused by the consumption of seafood (fish and marine invertebrates) contaminated with ciguatoxins (CTXs) produced by dinoflagellates in the genus Gambierdiscus. The report of a CFP-like mass-poisoning outbreak following the consumption of Tectus niloticus (Tegulidae, Gastropod) from Anaho Bay on Nuku Hiva Island (Marquesas archipelago, French Polynesia) prompted field investigations to assess the presence of CTXs in T. niloticus. Samples were collected from Anaho Bay, 1, 6 and 28 months after this poisoning outbreak, as well as in Taiohae and Taipivai bays. Toxicity analysis using the neuroblastoma cell-based assay (CBA-N2a) detected the presence of CTXs only in Anaho Bay T. niloticus samples. This is consistent with qPCR results on window screen samples indicating the presence of Gambierdiscus communities dominated by the species G. polynesiensis in Anaho Bay. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) analyses revealed that P-CTX-3B was the major congener, followed by P-CTX-3C, P-CTX-4A and P-CTX-4B in toxic samples. Between July 2014 and November 2016, toxin content in T. niloticus progressively decreased, but was consistently above the safety limit recommended for human consumption. This study confirms for the first time T. niloticus as a novel vector of CFP in French Polynesia.